Microwave-assisted ADMET polymerization (2015)
Microwave-assisted ADMET polymerization is reported on a series of α,ω-diene monomers, both polar and non-polar. Investigations indicate that of the multiple microwave modes possible, constant power is the most advantageous, providing polymers up to M‾w=31,000g/mol. Molecular weight values are nearly triple in comparison with conventional oil bath heating. Polymers are characterized by NMR, GPC, TGA, and DSC. Microwave irradiation provides a highly controllable and energy efficient ADMET polymerization technique.